1999
DOI: 10.1155/dte.5.119
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience Using a Real Time Autofluorescence Endoscopy System in the Gastrointestinal Tract

Abstract: Autofluorescence spectra of neoplastic tissues have been reported to be significantly different from those of normal tissues when excited by blue or violet light. From this concept, a lightinduced autofluorescence endoscopic imaging system for gastrointestinal mucosa (LIFE-GI; Xillix, Canada and Olympus, Japan) has been newly developed and the clinical evaluation of the prototype system has been conducted in hospitals in Canada, Netherlands and Japan.We examined the clinical usefulness of the prototype LIFE-GI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Ogihara et al studied the relationship between the color of the autofluorescence image and the histopathology of the biopsy specimens in colonic lesions. 15 Their results show that all of the nine adenocarcinoma studied appeared as dark red, and 38 out of 45 adenomas (84%) appeared as dark red, and the remaining adenomas appeared as light red. Watanabe et al described the clinical usefulness of the LIFE-GI system for patients with laterally spreading superficial tumors of the colon, which were sometimes difficult to detect by conventional white-light endoscopy, but were accurately diagnosed by this system.…”
Section: Clinical Experience Using Life-gi Systemmentioning
confidence: 91%
See 2 more Smart Citations
“…Ogihara et al studied the relationship between the color of the autofluorescence image and the histopathology of the biopsy specimens in colonic lesions. 15 Their results show that all of the nine adenocarcinoma studied appeared as dark red, and 38 out of 45 adenomas (84%) appeared as dark red, and the remaining adenomas appeared as light red. Watanabe et al described the clinical usefulness of the LIFE-GI system for patients with laterally spreading superficial tumors of the colon, which were sometimes difficult to detect by conventional white-light endoscopy, but were accurately diagnosed by this system.…”
Section: Clinical Experience Using Life-gi Systemmentioning
confidence: 91%
“…14 In a study by Ogihara et al all of 20 gastric cancers were dark red, three out of five gastric adenomas were light red, and the remaining two were dark red. 15 This system has also been applied to the detection of remnant lesions after endoscopic treatment of early gastric cancer. 15 Remnant lesions after endoscopic resection were suspected in four out of 12 lesions after using the LIFE-GI system, two of which were found by histological methods to be adenocarcinoma, but were not detected by conventional white-light endoscopy.…”
Section: Clinical Experience Using Life-gi Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the same system, Yano et al reported a sensitivity of 88% detection within a series of 59 gastric cancers 14 . In a study by Ogihara et al all of 20 gastric cancers were dark red, three out of five gastric adenomas were light red, and the remaining two were dark red 15 . This system has also been applied to the detection of remnant lesions after endoscopic treatment of early gastric cancer 15 .…”
Section: Clinical Experience Using Life‐gi Systemmentioning
confidence: 99%
“…Fiber bundle-based endoscopes—fiberscopes—may have poorer resolution than rigid scopes but have a much smaller cross section (≤1 mm), ease of sterilization, and simplicity of manufacture, and may serve as an adjunct modality for other high-resolution imaging tools. Fiberscopes are particularly well suited for fluorescence imaging since they can be made very small, use extremely sensitive detectors, such as intensified or electron-multiplying cameras, and can detect weak fluorescence signals through the working channels of existing clinical endoscopes [21]. Also, when used in conjunction with targeted molecular probes, the resolution of a fiberscope is less prohibitive and can reveal the presence of fluorescence signals—rather than relying on high-resolution morphological detail, and may be sufficient to guide further inspection with more high-resolution devices that have smaller fields of view, or to guide biopsy.…”
Section: Introductionmentioning
confidence: 99%